2014
DOI: 10.1007/s00216-014-7743-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of low molecular weight fatty acids in cave drip water and speleothems using HPLC-ESI-IT/MS — development and validation of a selective method

Abstract: This study presents a novel method for the analysis of low molecular weight (LMW) fatty acids in cave drip water and speleothems. The method development included optimization of sample preparation procedures, e.g., blank reduction, solid phase extraction, concentration of extracts as well as liquid chromatography coupled to electrospray ion-trap mass spectrometry (HPLC-ESI-IT/MS) measurement parameters. Retention times for five analytes (lauric acid, myristic acid, palmitic acid, stearic acid and arachidic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Since studies first demonstrated the presence of organic matter (OM) entrapped in calcite (Baker et al, 1996;Ramseyer et al, 1997), a number of organic components of speleothems being used as proxies for investigating changes in soils, vegetation, and climate (e.g., Baker et al, 1998;Blyth & Schouten 2013;Blyth et al 2011;Blyth et al, 2014;Bosle et al, 2014;Li et al, 2014;Perrette et al, 2005, Perrette et al, 2008Webb et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since studies first demonstrated the presence of organic matter (OM) entrapped in calcite (Baker et al, 1996;Ramseyer et al, 1997), a number of organic components of speleothems being used as proxies for investigating changes in soils, vegetation, and climate (e.g., Baker et al, 1998;Blyth & Schouten 2013;Blyth et al 2011;Blyth et al, 2014;Bosle et al, 2014;Li et al, 2014;Perrette et al, 2005, Perrette et al, 2008Webb et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The comparisons between the SBSE derivatization technique and other previously reported methods for measuring aqueous carbonyls in terms of LOD are listed in Table . The LODs of this SBSE technique for carbonyl measurements are lower than those of GC–ECD , and SPME–HPLC–UV , by 10 to 100 times and close to those of SBSE–HPLC–MS and solvent extraction GC–ECD techniques .…”
Section: Resultsmentioning
confidence: 51%
“…Peaks in GC chromatograms are formaldehyde (peak 1), PFBHA (peak 2), ethanal (peaks 3 and 4), acetone (peak 5), propanal (peaks 6 and 7), propenal (peak 8), butanal (peak 9), isobutenal (peak 10), butanone (peak 11), 2-hydroxy ethanol (peaks 12 and 13), pentanal (peak 14), hexanal (peaks 15 and 16), GLY (peaks 17, 18, and 19), and MGLY (peaks 20 and 21), respectively methods for measuring aqueous carbonyls in terms of LOD are listed in Table 4. The LODs of this SBSE technique for carbonyl measurements are lower than those of GC-ECD [28], and SPME-HPLC-UV [29], by 10 to 100 times and close to those of SBSE-HPLC-MS [30] and solvent extraction GC-ECD techniques [31].…”
Section: Calibrations and Detection Limitsmentioning
confidence: 54%
“…However, the focus on biomarkers extractable by wet chemistry from the carbonate means that most research to date has required relatively large sample sizes of calcite (1-100 g) ( [50,14,51,13,36]), compared to established inorganic geochemical proxies. Selected techniques published to date allow analysis of less than 1 g of calcite: thermochemolysis of lignin (0.5 g; [12,16]); one study of lipid biomarkers in an American stalagmite (0.3-0.5 g; [40]) amino acid analysis (25-120 mg, [35,15]); high performance liquid chromatography analysis of short chain fatty acids (0.5-3.5 g, [21]); and liquid chromatography-isotope ratio mass spectrometry (LC-IRMS) analysis of bulk organic isotopes (0.2 g; [18,19]). Of these, only LC-IRMS of bulk ı 13 C has so far been fully applied in a multi-proxy palaeoenvironmental reconstruction [19].…”
Section: Introductionmentioning
confidence: 99%